2015
DOI: 10.3233/ies-140563
|View full text |Cite
|
Sign up to set email alerts
|

Strength and torque consistency of the hip and knee flexors and extensors: A comparative study of elderly and young individuals

Abstract: OBJECTIVES: To assess the strength of the flexors and extensors of the knee and hip joints in elderly and in young individuals. METHODS: A group of elderly women (N = 47) and men (N = 44) aged 65 and older and a group of young women (N = 15) and men (N = 15) aged between 20 and 30 years were tested for the isokinetic strength of the hip and knee flexors and extensors. RESULTS: A typical age-related decrease in the strength of all tested muscles was observed but the decline in hip muscles strength, compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…These authors found that AAR was not different between groups for the 60°/s velocity, corroborating the results found in the present study. On the other hand, Borges et al (2015) 24 demonstrate higher peak torque values for hip and knee joints at 60, 120 and 180°/s angular velocities for adults compared to older adults that supports the idea of the effects of aging on torque production and movement velocity. Although the importance of resistance exercices for older adults is well elucidated in the literature, there is a divergence regarding the issue of execution of training to improve the maximum force (peak torque) and those that aim to improve the muscular power.…”
Section: Discussionmentioning
confidence: 78%
“…These authors found that AAR was not different between groups for the 60°/s velocity, corroborating the results found in the present study. On the other hand, Borges et al (2015) 24 demonstrate higher peak torque values for hip and knee joints at 60, 120 and 180°/s angular velocities for adults compared to older adults that supports the idea of the effects of aging on torque production and movement velocity. Although the importance of resistance exercices for older adults is well elucidated in the literature, there is a divergence regarding the issue of execution of training to improve the maximum force (peak torque) and those that aim to improve the muscular power.…”
Section: Discussionmentioning
confidence: 78%